Ammonia decomposition catalyst and preparation method thereof
By optimizing the pretreatment steps and preparation methods of biological templates, Ba-MgO support with high specific surface area and uniform morphology was prepared. Combined with ruthenium, the problem of insufficient activity of existing catalysts under low temperature conditions was solved, and efficient and stable ammonia decomposition catalysis was achieved.
Patent Information
- Application Number
- CN202411799725.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-09
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2044-12-09
Smart Images

Figure CN119588341A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of ammonia decomposition process, and specifically relates to an ammonia decomposition catalyst and a preparation method thereof. Background Art
[0002] Hydrogen energy is one of the clean energy sources with the greatest development potential, with outstanding advantages of high efficiency, cleanliness, and zero carbon and environmental protection. Among hydrogen production technologies, ammonia decomposition has the characteristics of high raw material conversion efficiency and no pollution, and is an ideal source of hydrogen. The traditional ammonia decomposition reaction still requires a reaction temperature of 800-850°C under the action of a catalyst, and has high energy consumption. Therefore, researchers hope to design a catalyst that can achieve low-temperature catalytic ammonia decomposition.
[0003] Ruthenium metal nanoparticles are a type of catalytically active component with excellent performance and can function at low temperature and low pressure. Ruthenium metal nanoparticles need to use metal oxides with rich pore structures as catalyst carriers, and the structural morphology of the carrier will also affect the catalytic effect of ruthenium. The bio-template method is a method for synthesizing metal oxide carriers. Its principle is to use natural biological materials with special structures as templates, and the adsorption, deposition and removal of metal ions on the templates make the metal oxides obtain a microscopic morphology similar to the biological template. In the inventor's previous patent CN 104289217 A, a method for preparing a ruthenium-based ammonia synthesis catalyst supported by a biological morphology composite oxide was proposed. The patent uses fir, filter paper, cotton fiber, amino acids or proteins as biological templates, and directly mixes the biological template with a metal salt solution for impregnation to obtain a catalyst carrier. The inventors further discovered that although this preparation method directly utilizing biological templates is simple and quick, it is limited by the number of active groups on the surface of the biological template, and the adsorption of metal ions can easily reach saturation. In addition, the prepared metal oxide carrier particles are uneven in size, and the specific surface area of the carrier is limited, which limits the loading capacity for active components, and the catalyst is prone to aging and inactivation. Summary of the invention
[0004] In view of this, the inventors hope to propose an optimized ammonia decomposition catalyst and a preparation method thereof, which improves the adsorption capacity of metal ions by optimizing the bio-template, thereby improving the microscopic morphology of the metal oxide carrier and increasing the specific surface area, so that the obtained catalyst product has a longer working life. On this basis, the ammonia decomposition catalyst also has a catalytic effect that is equivalent to or even better than that of the bio-template method before optimization.
[0005] The present invention is achieved through the following technical solutions: A method for preparing an ammonia decomposition catalyst, characterized in that it comprises at least the following steps: S1, mixing the biological template with reagent A and impregnating them, and obtaining an optimized biological template after drying; S2, mixing and impregnating the optimized biological template with reagent B, drying and then calcining to obtain a catalyst carrier; S3, mixing and impregnating the catalyst support with reagent C, and drying to obtain a catalyst precursor; S4, activating the catalyst precursor to obtain the ammonia decomposition catalyst.
[0006] The reagent A contains carboxylic acid, the duration of the mixed impregnation in S1 is 1 to 24 hours, and the temperature of the mixed impregnation in S1 is 20 to 80° C.; The reagent B is a solution containing at least magnesium ions and barium ions; The catalyst carrier is a Ba-MgO carrier; The reagent C contains 0.2 wt% to 5 wt% of ruthenium element.
[0007] S1 of the present technical solution is a pretreatment step, which aims to optimize the microstructure of the biological template; S2 is a preparation step of a metal oxide carrier, in which metal ions are adsorbed and deposited on the surface of the optimized biological template by impregnation, and a biological metal oxide Ba-MgO carrier is obtained after drying and calcination; S3 is an active component loading step, in which the active component ruthenium contained in reagent C is dispersed and loaded on the Ba-MgO carrier; S4 is an activation step, in which the catalytic activity of ruthenium is fully released.
[0008] Preferably, the reagent A comprises a hydrogen ion donor reagent for adjusting the abundance of hydrogen ions in the reagent A.
[0009] Preferably, the reagent A is a 1:4 (v:v) mixed solution of 3 mol / L hydrochloric acid solution and 3 mol / L acetic acid solution.
[0010] Preferably, the concentration of magnesium ions in the reagent B is 0.1-0.8 mol / L, and the molar ratio of magnesium ions to barium ions is 100-180:1.
[0011] Preferably, the reagent B is an acetate solution.
[0012] Preferably, the temperature of the mixed impregnation in S1 is 50-80°C, Preferably, the mixed impregnation time in S1 is 1 to 5 hours.
[0013] Preferably, the biological template is plant fiber. Cellulose in plant fiber has a multi-layered network structure and a high specific surface area, and is an excellent biological template; cellulose is a macromolecular polysaccharide composed of glucose, and there are hydroxyl groups in the structure, which can be combined with inorganic substances and replicate the morphology; cellulose mainly contains carbon, hydrogen, and oxygen elements, and does not contain other elements that poison the catalyst, and as a biological template, it is easy to remove and does not affect the catalytic activity of the final catalyst.
[0014] Preferably, the reagent C is Ru 3 (CO) 12 The reagent C is used to load the catalytically active ruthenium element onto the catalyst support. During the impregnation process, Ru 3 (CO) 12 After the loading of ruthenium is completed, in the subsequent activation process, Ru 3 (CO) 12 It can decompose in the low temperature zone, ruthenium remains in the carrier, and the remaining elements are converted into CO and removed without introducing other adverse elements.
[0015] The present invention also includes an ammonia decomposition catalyst, characterized in that it is prepared by any of the preparation methods described above.
[0016] The present invention has the following beneficial effects: 1. Catalyst performance The present invention proposes a Ba-MgO-supported ruthenium-based ammonia decomposition catalyst based on a pretreated biological template. The catalyst can achieve high catalytic activity under low temperature and normal pressure conditions, greatly reducing the difficulty of ammonia decomposition reaction. Experimental results show that the ammonia decomposition catalyst obtained by the present invention can achieve high catalytic activity under low temperature and normal pressure conditions at 450 ° C, normal pressure, and 7800 h -1 The ammonia decomposition catalyst prepared by the preferred parameters can even increase the conversion rate to more than 99%. The ammonia decomposition catalyst produced by the present invention is also stable and can withstand temperatures of 450 °C and 10,000 h. -1 After continuous testing for 100 hours under the same conditions, the catalytic performance did not change significantly.
[0017] 2. Preparation method Compared with the prior art, the present invention improves the structure of the biological template by adding a pretreatment step. The present invention has extensively experimentally compared the parameters of the pretreatment step and their optimization, and these parameters have also formed a mutually reinforcing relationship, so that the biological template can adsorb and bind more metal ions, and finally construct a metal oxide carrier with a larger specific surface area and better uniformity. Its principles include: 2.1. The biological template is a cellulose polymer. The hydrogen ions in reagent A can penetrate into the β-1,4-glycosidic bonds of the cellulose molecules, breaking the long cellulose chains and exposing the hydroxyl groups inside the polymer. The magnesium ions and barium ions combine with the hydroxyl groups on the cellulose, which is conducive to the Ba-MgO metal oxide carrier to more accurately and fully replicate the morphology of the biological template; 2.2. Reagent A is an acidic solution containing carboxylic acid and hydrogen ions. After the hydrogen ions open the long cellulose chains, the carboxyl groups can enter the interior of the cellulose polymer, causing the cellulose to swell, which is conducive to the further penetration of the hydrogen ions. When only carboxylic acid is present, the degree of hydrogen ion ionization is low, and the degree of opening of the cellulose long chains is limited. When only strong acid hydrogen ions are present, the hydrogen ions are likely to cause excessive hydrolysis of cellulose, and the hydrogen ions cannot fully penetrate into the long chains. When the carboxyl groups and hydrogen ions work together, they can promote each other and fully expose the hydroxyl groups on the cellulose. 2.3. Reagent B contains acetate, which is easy to combine with cellulose and can be removed together with the bio-template during the calcination process. Acetate also has a large ionic radius, which will leave more vacancies during the removal of the bio-template, thereby increasing the specific surface area of its bio-morphological Ba-MgO carrier and thus improving the ammonia decomposition activity of the catalyst. 2.4.S1 The temperature of the mixed impregnation is controlled at 60-80°C and the duration is controlled at 2-3 hours, which can make the hydrolysis degree of cellulose in the best state, neither causing excessive hydrolysis of cellulose nor promoting the synergistic effect of hydrogen ions and carboxyl groups, thereby improving the ammonia decomposition activity of the catalyst; 2.5. The aforementioned technical means 2.1 to 2.4 optimize the proportion and dispersion of the promoter barium in the carrier by treating the biological template, which is beneficial to the dispersion of the catalyst active component ruthenium in the subsequent steps, and helps to enhance the strong interaction between ruthenium and the biological form Ba-MgO carrier, thereby improving the activity and stability of the catalyst.
[0018] In addition, the preparation method proposed in the present invention reduces the use of strong acid and shortens the pretreatment time through mild heating treatment and the addition of carboxylic acid, which complies with the national policy of energy conservation and emission reduction; the incorporation of the auxiliary agent barium and the preparation of the carrier are completed in one step, the steps are simple, practical and have industrial prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 This is a catalyst stability test diagram; Figure 2 FE-SEM images of the bio-template morphology at each stage of the experiment; Figure 3 FE-SEM images of each bio-template and bio-morphological Ba-MgO support; Figure 4 FE-SEM images of cotton fibers after treatment with different reagents A. DETAILED DESCRIPTION
[0020] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments of the specification. Those of ordinary skill in the art will be able to implement the present invention based on these descriptions. In addition, the embodiments of the present invention involved in the following description are generally only embodiments of a part of the present invention, rather than all embodiments. Therefore, based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work should fall within the scope of protection of the present invention.
[0021] 1. Experimental Protocol 1.1 Reagent preparation 3mol / L hydrochloric acid solution; 3mol / L acetic acid solution; Magnesium acetate-barium acetate solution, the preparation method in this experiment is: according to n(Mg 2+ )∶n(Ba 2+ )=166∶1 Weigh magnesium acetate and barium acetate, dissolve them in distilled water to obtain Mg 2+ Aqueous solution with a concentration of 0.3 mol / L.
[0022] The magnesium nitrate-barium nitrate solution is prepared as follows: 2+ )∶n(Ba 2+ )=166∶1 Weigh magnesium nitrate and barium nitrate, dissolve them in distilled water to obtain Mg 2+ Aqueous solution with a concentration of 0.3 mol / L.
[0023] Ruthenium content 2wt% 3 (CO) 12 tetrahydrofuran solution; In other embodiments, the magnesium salt-barium salt solution may be in the form of other acid radicals such as other chloride salts, the molar ratio of magnesium ions to barium ions may be in the range of 100 to 180:1, and the concentration of magnesium ions may be in the range of 0.1 to 0.8 mol / L; Ru 3 (CO) 12 The ruthenium content in the tetrahydrofuran solution can be in the range of 0.2wt% to 5wt%.
[0024] 1.2 Experimental parameter design Table 1 summarizes the parameter differences between the comparative examples and the embodiments, and the numbering sequence of the embodiments is associated with the parameter optimization ideas.
[0025] Table 1 Parameter design of each comparative example and embodiment S1 Biological Template S1 Reagent A S1 immersion time S1 immersion temperature S2 Reagent B in salt form Comparative Example 1 Wheat straw water 24h Room temperature (20°C) Acetate Comparative Example 2 Cotton Fiber water 24h Room temperature (20°C) Acetate Comparative Example 3 Cotton Fiber water 24h Room temperature (20°C) Nitrates Example 1 Cotton Fiber hydrochloric acid 24h Room temperature (20°C) Acetate Example 2 Cotton Fiber Acetic acid 24h Room temperature (20°C) Acetate Example 3 Cotton Fiber hydrochloric acid 2h 80℃ Acetate Example 4 Cotton Fiber hydrochloric acid 3h 80℃ Acetate Example 5 Cotton Fiber Acetic acid 24h 80℃ Acetate Example 6 Cotton Fiber Hydrochloric acid: acetic acid 1:1 (v:v) mixture 2h 80℃ Acetate Example 7 Cotton Fiber Hydrochloric acid: acetic acid 1:4 (v:v) mixture 2h 80℃ Acetate Example 8 Cotton Fiber Hydrochloric acid: acetic acid 1:4 (v:v) mixture 2h 60℃ Acetate 1.3 Experimental process Comparative Example 1 This comparative example and comparative example 2 form a control relationship with "biological template" as a variable, and comparative example 2 is relatively preferred.
[0026] S1. Mix sufficient amount of wheat straw with deionized water and soak at room temperature for 24 hours; wash the wheat straw with deionized water until it is neutral, and dry it at 110°C; S2, take 400mL of magnesium acetate-barium acetate solution, weigh the wheat straw obtained in S1 with the same mass as magnesium acetate, mix and soak for 48 hours, and then dry at 110°C for 12 hours; calcine in a muffle furnace at 600°C for 3 hours to obtain a biomorphic Ba-MgO carrier; S3, the biological Ba-MgO carrier obtained in S2 and the Ru content of 2wt% 3 (CO) 12 The mixture was immersed in tetrahydrofuran solution for 12 hours; the solvent was evaporated in a water bath and dried in an oven at 60°C; S4, vacuum treatment at 450 ° C in a tube furnace for 3 hours, 2 Cool to room temperature in atmosphere; S5. Tableting, crushing and screening to obtain the ammonia decomposition catalyst in a usable form.
[0027] Comparative Example 2 The difference between this comparative example and comparative example 1 is that the biological template used in this comparative example S1 is cotton fiber; the other steps and parameter operations are the same as those in comparative example 1.
[0028] This comparative example and comparative example 1 form a control relationship with "biological template" as a variable; the results show that cotton fiber is relatively preferred as the "biological template".
[0029] Comparative Example 3 The difference between this comparative example and comparative example 2 is that the reagent B used in this example S2 is a magnesium nitrate-barium nitrate solution; the other steps and parameter operations are the same as those in comparative example 2.
[0030] This comparative example and comparative example 2 form a control relationship with "salt form of reagent B" as a variable; the results show that acetate is relatively preferred as reagent B.
[0031] Example 1 The difference between this embodiment and comparative example 2 is that: in this embodiment S1, reagent A is used for mixed impregnation with the biological template, and the reagent A used is 3 mol / L hydrochloric acid solution; the other steps and parameters are the same as those in comparative example 2.
[0032] This embodiment and comparative example 2 form a comparison relationship with "whether to use reagent A for impregnation" as a variable; the results show that impregnation with reagent A is relatively preferred; Example 2 The difference between this embodiment and embodiment 1 is that the reagent A used in embodiment S1 is 3 mol / L acetic acid solution; the other steps and parameters are the same as those in embodiment 1.
[0033] This example forms a control relationship with Example 1 with "hydrogen ion concentration of reagent A" as a variable; the results show that a higher hydrogen ion concentration is relatively preferred. Hydrogen ions can destroy the -CO-glycosidic bonds between adjacent glucose monomers on cellulose, break the long cellulose chains, and expose more active hydroxyl groups.
[0034] Example 3 The difference between this embodiment and embodiment 1 is that the use condition of reagent A in this embodiment S1 is immersion at 80° C. for 2 hours; the other steps and parameters are the same as in embodiment 1.
[0035] This example forms a comparison relationship with Example 1 with "immersion temperature of reagent A" and "immersion time of reagent A" as variables; the results show that short-term heating treatment can improve the ammonia conversion rate of the obtained catalyst in a working environment below 450°C. The reason is that heating can promote the expansion of cellulose and make it loose, which is conducive to the entry of hydrogen ions into the interior of the cellulose long chain.
[0036] Example 4 The difference between this embodiment and embodiment 3 is that the use condition of reagent A in embodiment S1 is immersion at 80° C. for 3 hours; the other steps and parameters are the same as those in embodiment 3.
[0037] This example forms a comparison relationship with Example 3 with "immersion time under heating conditions" as a variable; the results show that under heating conditions, further extending the immersion time will reduce the ammonia conversion rate of the catalyst in an operating environment below 450°C. The reason may be that long-term heating causes excessive hydrolysis of cellulose and damages the internal structure.
[0038] Example 5 The difference between this embodiment and embodiment 2 is that the use condition of reagent A in embodiment S1 is immersion at 80° C. for 24 hours; the other steps and parameters are the same as those in embodiment 2.
[0039] This example and Example 2 form a comparative relationship with "immersion temperature during acetic acid treatment" as a variable; the results show that when the same acid is used for treatment, a higher immersion temperature is relatively preferred.
[0040] Example 6 The difference between this embodiment and embodiment 3 is that the components of reagent A in embodiment S1 are 3 mol / L hydrochloric acid solution: 3 mol / L acetic acid solution in a ratio of 1:1; the other steps and parameters are the same as those in embodiment 3.
[0041] This example and Example 3 form a control relationship with "whether the acidic environment contains carboxyl groups" as the variable; the results show that the addition of carboxyl groups is a preferred condition.
[0042] Example 7 The difference between this embodiment and embodiment 6 is that the components of reagent A in embodiment S1 are 3 mol / L hydrochloric acid solution: 3 mol / L acetic acid solution in a ratio of 1:4; the other steps and parameters are the same as those in embodiment 6.
[0043] This example and Example 6 form a control relationship with "the content of carboxyl groups in an acidic environment" as a variable; the results show that when the hydrogen ion content is sufficient, the increase in the carboxyl content is the preferred condition.
[0044] Example 8 The difference between this embodiment and embodiment 7 is that the immersion temperature of reagent A in embodiment S1 is 60° C.; the other steps and parameters are the same as those in embodiment 7.
[0045] This example and Example 7 form a control relationship with "immersion temperature of reagent A" as a variable; combined with the conclusion of Example 5, the component of reagent A is a relatively major factor affecting the catalytic efficiency of the product of the example, and the immersion temperature is a relatively minor factor.
[0046] 2. Experimental results 2.1 Catalytic efficiency evaluation The activity of the ammonia decomposition catalysts prepared in Comparative Examples 1 to 3 and Examples 1 to 8 was evaluated in a fixed bed reactor. The inner diameter of the reaction tube was 8 mm, the length of the dynamic isothermal zone was 30 mm, and the catalyst was loaded in the isothermal zone. The reaction temperature was 300 to 500° C., the reaction pressure was atmospheric pressure, and the reaction volume space velocity was 7800 h -1 The raw gas is 99.999% high-purity ammonia. The ammonia concentration of the reactor outlet gas (expressed as volume percentage, vol%) was measured by sulfuric acid solution neutralization method as an activity evaluation index of the catalyst. The experimental results are shown in Table 2.
[0047] Table 2 Comparison of ammonia conversion rates of comparative examples and examples at different temperatures As shown in Table 2, Example 7 has the best catalytic efficiency at 450°C, even reaching 99.65%. The corresponding optimal technical solution is: in S1, cotton fiber is used as a biological template, 3mol / L hydrochloric acid: 3mol / L acetic acid 1:4 is used as reagent A, and it is immersed at 80°C for 2 hours; in S2, magnesium acetate-barium acetate solution is used as reagent B; other steps and parameters are the same as comparative example 1. Example 1 can still achieve a catalytic efficiency of more than 90% at a temperature of 500°C. At this time, the corresponding pretreatment parameters are immersion in 3mol / L hydrochloric acid for 24h at room temperature (20°C); analysis shows that increasing the immersion temperature can simultaneously achieve the effect of shortening the immersion time and improving the catalytic efficiency. Therefore, the preferred value range of this technical solution can be further expanded, that is, the immersion temperature range is 50~80°C, and the mixed immersion time is 1~5h.
[0048] 2.2 Catalyst stability evaluation According to the experimental results of 2.1, the ammonia decomposition catalyst prepared in Example 7 has the best activity, and a stability test was performed on it. Figure 1 As shown, at 450 °C, 10000 h -1 Under the same conditions, the conversion rate of the catalyst was stably maintained at about 98%, and the catalytic performance did not change significantly within 100 hours. The principle may be that the biomorphic Ba-MgO carrier has more uniform and complete nanoparticles, with a larger specific surface area, which can better disperse the active component ruthenium, thereby effectively inhibiting the sintering of ruthenium at high temperature and causing catalyst deactivation.
[0049] 2.3 Morphological characterization Figure 2 The following are field emission scanning electron microscopy (FE-SEM) images of the bio-template morphology at each stage of the experiment. 2-A is the original cotton fiber, 2-B is the cotton fiber treated with a mixture of hydrochloric acid and acetic acid, and 2-C is the bio-morphological Ba-MgO carrier with 2-B as the bio-template. The SEM image shows that after the hydrochloric acid-acetic acid mixture treatment, the impurities on the cotton fiber surface are removed, exposing more wrinkles. The Ba-MgO carrier prepared with this as the bio-template has a more uniform spherical nano-morphology, which can better load and disperse the active component ruthenium.
[0050] Figure 3 FE-SEM images of various bio-templates and bio-morphological Ba-MgO carriers. 3-A is original wheat straw, 3-B is wheat straw impregnated with 3 mol / L hydrochloric acid at room temperature for 24 hours, 3-C is a bio-morphological Ba-MgO carrier prepared with 3-B as a bio-template; 3-D is original cotton fiber, 3-E is cotton fiber impregnated with 3 mol / L hydrochloric acid at 60°C for 2 hours, and 3-F is a bio-morphological Ba-MgO carrier prepared with 3-E as a bio-template.
[0051] Figure 4 FE-SEM images of cotton fibers after treatment with different reagents A. 4-A is the result of treatment with 1 mol / L acetic acid, 4-B is the result of treatment with 3 mol / L acetic acid, 4-C is the result of treatment with 1 mol / L hydrochloric acid, and 4-D is the result of treatment with 3 mol / L hydrochloric acid.
Claims
1. A method for preparing an ammonia decomposition catalyst, characterized in that: At least the following steps are included: S1, mixing the biological template with reagent A and impregnating them, and obtaining an optimized biological template after drying; S2, mixing and impregnating the optimized biological template with reagent B, drying and then calcining to obtain a catalyst carrier; S3, mixing and impregnating the catalyst support with reagent C, and drying to obtain a catalyst precursor; S4, activating the catalyst precursor to obtain the ammonia decomposition catalyst; The reagent A contains carboxylic acid, the duration of the mixed impregnation in S1 is 1 to 24 hours, and the temperature of the mixed impregnation in S1 is 20 to 80° C.; The reagent B is a solution containing at least magnesium ions and barium ions; The catalyst carrier is a Ba-MgO carrier; The reagent C contains 0.2 wt% to 5 wt% of ruthenium element.
2. The preparation method according to claim 1, characterized in that: The reagent A comprises a hydrogen ion donor reagent.
3. The preparation method according to claim 2, characterized in that: The reagent A is a 1:4 (v:v) mixed solution of 3 mol / L hydrochloric acid solution and 3 mol / L acetic acid solution.
4. The preparation method according to claim 1, characterized in that: The concentration of magnesium ions in the reagent B is 0.1-0.8 mol / L, and the molar ratio of magnesium ions to barium ions is 100-180:
1.
5. The preparation method according to claim 1, characterized in that: The reagent B is an acetate solution.
6. The preparation method according to claim 1, characterized in that: The temperature of the mixed impregnation in S1 is 50-80°C.
7. The preparation method according to claim 1, characterized in that: The duration of the mixed impregnation in S1 is 1 to 5 hours.
8. The preparation method according to claim 1, characterized in that: The biological template is plant fiber.
9. The preparation method according to claim 1, characterized in that: The reagent C is Ru3(CO) containing 2 wt% ruthenium. 12 of tetrahydrofuran solution.
10. An ammonia decomposition catalyst, characterized in that: The method is carried out by the method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Preparation method of biological graded porous structure composite semiconductor visible-light photo-catalytic material
CN103055955A
Biomorphic-composite-oxide loaded ruthenium catalyst for ammonia synthesis and preparation method thereof
CN104289217A
Ammonia synthesis catalyst taking ruthenium acetate as precursor and preparation method thereof
CN111185164A
Preparation method of ruthenium-based catalyst
CN111229213A
Alkaline-earth metal oxide supported ruthenium catalyst, and preparation method and application thereof
CN112973679A